Challenges and trends in modern banking - Queen's University (Kingston, Ont.); Canadian Bankers' Association (Toronto : Canadian Bankers Association, 1967)
"Challenges and Trends in Modern Banking" was the theme of the 20th International Banking Summer School held at Montreal, Queen's University, Kingston, and Toronto during August 1967. The lectures, delivered to an audience of bankers from 52 countries, provided a forum for an enlightened study of current methods and techniques and for a preview of future expectations in these fields. It also reflected the increasingly important role of banks in national economies and international finance, and emphasized the need for the banks to recognize fully the rapid rate of change occasioned by improved communication systems and automation.
Bibliography: p. 100-101.
rpm 30/04/2018
Loans
Keywords: Banks and banking